Benefits and Risks of Epilepsy Surgery in Patients With Focal Cortical Dysplasia Type 2 in the Central Region. (5th July 2022) - Chassoux, Francine; Mellerio, Charles; Laurent, Agathe; Landre, Elisabeth; Turak, Baris; Devaux, Bertrand
Abstract : Background and Objectives: Focal cortical dysplasia type 2 (FCD2 ) in the central region can cause drug-resistant epilepsy for which surgery remains challenging because of subsequent functional deficits. Advances in imaging and surgical techniques have progressively improved outcome. We aimed to assess the benefits on epilepsy and the functional risks after FCD2 resections in these highly eloquent areas. Methods: We retrospectively studied all consecutive patients with histologically confirmed FCD2 located in the central region operated on between 2000 and 2019 at a single center. We analyzed electroclinical and imaging features (including fMRI), seizure outcome, and early and late postoperative neurologic status correlating to anatomo-functional areas (primary motor cortex [PMC], paracentral lobule [PCL], supplementary motor area [SMA], precentral gyrus [PrCG], postcentral gyrus [PoCG], central operculum [COp]). Results: Sixty patients (35 female, age 7–65 years) were included in the study. Epilepsy was characterized by early onset, high seizure frequency with clusters (30–90/d), drop attacks, and status epilepticus. Ictal semiology included sensory-motor auras, motor and postural manifestations, and postictal motor deficits. EEG and stereo-EEG patterns were like those typically recorded in FCD2 . MRI was positive in 63% and 18 F-fluorodeoxyglucose-PET was positive in 86% of the patients. fMRI demonstrated activations close to the FCD2 (59%) or minor reorganization (41%) but none within the lesion. Seizure-free outcome (2- to 20-year follow-up) was obtained in 53 patients (88%), including 37 achieving Engel class IA (62%), correlating with complete FCD2 removal. Early transitory postoperative deficits occurred in 52 patients (87%), which were severe in 19, mostly after PMC, PCL, and SMA resections, while PrCG, PoCG, and COp resections were associated with minor/moderate deficits. Total recovery was observed in 21 of 52 patients (40%), while a permanent deficit (>2 years) persisted in 31 (minor 19, moderate 9, major 3). The best outcome (seizure freedom without deficit [48%] or with minor deficit (28%]) was significantly more frequent in children ( p = 0.025). Antiseizure medications were discontinued in 28 patients (47%). Quality of life correlated with seizure-free outcome and absence of postoperative deficit; 43 patients (72%) reported a schooling or socio-professional improvement. Discussion: Excellent seizure outcome and low rates of major permanent disability can be achieved after central FCD2 resections despite functional risks. Classification of Evidence: Due to its retrospective nature, this study provides Class IV evidence that good seizure outcomes with minor additional deficits can be achieved after epilepsy surgery in the central region.